DOŚWIADCZENIA OSOBISTE ORAZ PERSPEKTYWA ŻYCIA PODCZAS OKUPACJI W RELACJACH BIOGRAFICZNYCH POLSKICH TATARÓW Z LAT 1939-1945. WYBRANE ZAGADNIENIA - Łyszczarz, Michał (Przegląd Wschodnioeuropejski, 2024)
The paper analyses memories of life experiences from the time of World War II, present in the social consciousness of Polish Tatars. The memories of representatives of this small ethnic group have been preserved through personal documents (including diaries and memoirs), which have been made public and published in print. The content analysis included a collection of sources consisting of 13 items. The following issues have been discuss in detail: 1) assessment of the German occupation and the attitude of the Tatars towards the Nazis; 2) the Tatar experiences of exile and Soviet captivity; 3) the reactions of the Tatars to the outbreak of the Soviet-German war in 1941; 4) two visions of the future after the end of the war – repatriation to the Western Territories of Poland or emigration to Great Britain.